Pengaruh Daya Tarik Wisata, Aksesibilitas, Fasilitas, dan Electronic Word of Mouth Terhadap Keputusan Berkunjung Wisatawan di Agrowisata Eptilu - Miranda, Miranda; Awaliyah, Fitri; Adinasa, Muhamad Nu’man; Febrianti, Tintin (Hasanuddin University, 2024)
This study aims to determine the influence of tourist attraction, accessibility, facilities, and electronic word of mouth on the decision to visit Eptilu Agrotourism in the Garut Regency. The sampling method uses non-probability sampling with the technique used accidental sampling. The study sample was visitors to Eptilu Agrotourism as many as 50 respondents. Data collection using primary data in questionnaires distributed to visitors and secondary data obtained from literature studies in books, theses, journals, and the internet. The analysis method used is multiple linear regression analysis with SPSS 23 software. The analysis results show that tourist attractions, facilities, and electronic word of mouth influence visiting decisions. Accessibility does not influence visiting decisions.